The Role of Information Technology on the Effectiveness of Internal Control in Fraud Prevention - Randi Sastrawan; Mediaty; Amiruddin (Agency Journal of Management and Business, 2024)
Fraud or Fraud is a deliberate act of dishonesty to deprive another person/party of their rights or property. In the context of a financial statement audit, fraud is defined as a misstatement in a financial report carried out intentionally. Companies identified as committing fraud can result in bankruptcy. This is where the role of an internal control system is really needed. To reduce the potential for fraud committed by irresponsible parties, maximizing the role of information technology is one way that must be taken to prevent fraud. In this research, qualitative research methodology was used. This type of research is library research. The approach used in this research is a philosophical and pedagogical approach. In the process of preventing and detecting fraud, the use of information technology to strengthen the internal control system is a step to overcome this problem. Through the use of information technology systems, it is believed that it will reduce the occurrence of fraud in an organization, which of course will have a good impact on the continuity of the organization's business.